The Seventh Biennial Berry Health Benefits Symposium. Issue 1 (16th January 2018) - Seeram, Navindra P.; Burton-Freeman, Britt
Abstract : Guest Editors Navindra Seeram and Britt Burton-Freeman introduce the themed issue on work presented at the Seventh Biennial Berry Health Benefits Symposium, held in California, US. Abstract : Research advancing current scientific understanding of the health benefits of berries continues to increase. The Berry Health Benefits Symposium (BHBS) is a biennial meeting highlighting the most recent berry health benefits research from all over the world. Pismo Beach, California was the venue for the seventh biennial BHBS in 2017, and featured oral invited papers on heart health and healthy aging, gut/microbiome health, brain aging, inflammation, cancer prevention, berry special topics, technology and chemistry. These thematic health areas, while not exhaustive, characterize the state of berry health benefits science. The advancing field now encompasses human efficacy trials along with the most recent animal model and cell culture work elucidating mechanisms of action. Similar to past meetings, the research findings at the 2017 BHBS primarily focused on blackberries, blueberries, red raspberries, black raspberries, cranberries, and strawberries. However, research on other berry fruits, such as chokeberry (aronia berry), cloudberry, and bilberry were also covered. The BHBS continues to be a leading forum for interactions between scientists and berry industry stakeholders. The cluster of papers in this issue represents a snapshot of presentations at the 2017 BHBS, which support the positive biological effects of berries on human health and disease risk reduction.